2010
DOI: 10.1038/nmeth.1482
|View full text |Cite
|
Sign up to set email alerts
|

Single-allele analysis of transcription kinetics in living mammalian cells

Abstract: We generated a system for in vivo visualization and analysis of mammalian mRNA transcriptional kinetics of single alleles in real time, using single-gene integrations. We obtained high-resolution transcription measurements of a single cyclin D1 allele under endogenous or viral promoter control, including quantification of temporal kinetics of transcriptional bursting, promoter firing, nascent mRNA numbers and transcription rates during the cell cycle, and in relation to DNA replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
160
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(165 citation statements)
references
References 21 publications
5
160
0
Order By: Relevance
“…1A) is supported by a comprehensive large-scale study in bacteria, demonstrating that >400 genes appear to follow constitutive (or Poisson-like) gene expression (1). Constitutive expression has also been reported for subsets of human genes (2). Conversely, several elegant studies showed that specific promoters in bacteria and yeast express gene products in an episodic process (Fig.…”
mentioning
confidence: 69%
“…1A) is supported by a comprehensive large-scale study in bacteria, demonstrating that >400 genes appear to follow constitutive (or Poisson-like) gene expression (1). Constitutive expression has also been reported for subsets of human genes (2). Conversely, several elegant studies showed that specific promoters in bacteria and yeast express gene products in an episodic process (Fig.…”
mentioning
confidence: 69%
“…This resolution of detecting transcription and pausing cannot be obtained when examining single genes. 39 Interestingly, RNA Pol I transcription rates in the natural tandem rDNA array system of the nucleolus were also significantly higher (5.7 kb/min) than previous measurements. 40 Still, one might wonder whether the higher rate of Pol II transcription was specific for this artificial gene.…”
Section: Cell Systems For Following Transcription In Living Cellsmentioning
confidence: 54%
“…These "transcriptional bursts" amount to "memory" between transcripts: The synthesis of one transcript is likely to be accompanied by the synthesis of another over certain time intervals. Transcriptional bursting has now been observed in yeast (Zenklusen et al 2008;Lenstra et al 2015), slime mold (Chubb et al 2006;Muramoto et al 2010;Stevense et al 2010), fly (Garcia et al 2013), mouse , and human (Yunger et al 2010) cell lines and is a significant source of expression variation between cells. In fact, subsequent steps of gene expression such as RNA export, RNA decay, translation, etc.…”
Section: Transcriptional Burstingmentioning
confidence: 99%